Measurement of Security Awareness Level in the Implementation of Quick Response Code Indonesian Standard - Oktiana, Milda Safrila; Tarigan, Avinanta (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2025)
Quick Response Code Indonesian Standard (QRIS) is a QR code standard adopted in Indonesia as an electronic payment method. QRIS allows users to make payment transactions easily using mobile phones. Although QRIS provides many benefits regarding ease and efficiency of transactions, there are some security risks from payment methods using QR codes. A lack of public awareness regarding the safety of using QRIS can open the risk of misuse by irresponsible parties. This study aims to measure the level of security awareness in using QRIS Merchants in the DKI Jakarta areaThe research data was collected using questionnaires based on the Kruger and Kearney models involving 3 (three) dimensions, namely knowledge, attitudes, and behavior, as well as 6 (six) focus areas. The number of samples obtained was 110 respondents. The results showed that the safety awareness of QRIS use in the DKI Jakarta area was 91, in the average value category. With an average score of 91, most respondents realize the importance of paying attention to security aspects in transacting using QRIS.